(untitled) (Research, Society and Development, 2021)
The evolution of customs, human need and contemporary means of production require an enormous amount of energy, such a production model applied by society leads to an accelerated pace in the extraction of natural resources, renewable energies appear as a mitigation of impacts on the environment. climate and the environment, for a substitution of non-renewable energy sources to occur for renewable energy sources seeking to mitigate the emission of greenhouse gases - GHG, projects such as the Clean Development Mechanism (CDM) are necessary, enabling the commercialization of carbon, thus helping developing countries on a path towards sustainable development and using energy from renewable sources as a tool to reduce emissions, the general objective of the work was to evaluate the use of renewable energy as a tool for environmental services aiming at mitigation of climate change. The methodology consisted of information obtained from documents and reports, from the official websites of the United Nations Framework Convention on Climate Change (UNFCCC), Center for Energy, Climate and Sustainable Development (UNEP DTU Partnership - CDM pipeline) and the National Agency of Electricity (ANEEL), in the results we identified a great difference between the projects in operation when related to the registrations in the CDM, and there were only two peaks of registrations of projects being in 2006 and 2012, the lack of registrations of the Brazilian projects can be give due to its complexity, bureaucracy, or uncertainty of its continuity given an uncertain future.